Pregnancy outcomes in women with a systemic right ventricle and transposition of the great arteries. Results from the ESC-EORP Registry of Pregnancy and Cardiac disease (ROPAC). (25th November 2020) - Tutarel, O; Baris, L; Johnson, M; Hall, R; Roos-Hesselink, J.W
Abstract: Background: Cardiac disease is one of the major causes of maternal mortality. We studied pregnancy outcomes in women with a systemic right ventricle (sRV) after the atrial switch procedure for transposition of the great arteries (TGA) or congenitally corrected TGA (CCTGA). Methods: The ESC-EORP Registry of Pregnancy and Cardiac Disease is an international prospective registry of pregnant women with cardiac disease. Pregnancy outcomes (maternal and fetal) in women with a sRV are described. The primary endpoint was a major cardiovascular event (MACE) defined as maternal death, supraventricular or ventricular arrhythmias requiring treatment, heart failure, aortic dissection, endocarditis, ischemic coronary event and other thromboembolic events. Results: Altogether, 163 women with a sRV (TGA n=121, CCTGA n=42, mean age 28.8±4.6 years) were included. Maternal mortality did not occur. At least one MACE occurred in 26 women (heart failure in 16 (9.8%), arrhythmias (atrial 5, ventricular 6) in 11 (6.7%), and others in 4 (2.5%)). Predictors of MACE were pre-pregnancy signs of heart failure [Odds ratio (OR) 6.05, 95% CI: 1.41–25.97, p=0.02] as well as a sRV ejection fraction below 40% [OR 2.81, 95% CI: 1.18–6.69, p=0.02]. One woman experienced fetal loss, while no neonatal mortality was observed. No significant differences were found between women with CCTGA and TGA. In the subset of women who had an echocardiogram before and after pregnancy, no clear deterioration in sRV was observed. Conclusion: The majority of women with a sRV tolerated pregnancy well with a favorable maternal and fetal outcome. Heart failure and arrhythmias were the most common MACE. Funding Acknowledgement: Type of funding source: None